PENERAPAN ASAS ITIKAD BAIK TAHAP PRAKONTRAKTUAL PADA PERJANJIAN JUAL BELI PERUMAHAN - Antari Innaka; Sa’ida Rusdiana; Mr. Sularto (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2012)
The good faith principle is present in the pre-contractual stage of Preliminary House Sale and Purchase Agreement because all three contractual stages are also characterised by good faith. This Preliminary Agreement precedes the actual House Sale and Purchase Agreement and we submit that the Preliminary Agreement is legally binding provided that it be honestly entered to. The legal remedy that is available for consumers who find the promises of their property agent in the Preliminary Agreement not included in the actual House Sale and Purchase Agreement is the Decree of State Minister for Public Housing No. 09/KPTS/M/1995. Asas itikad baik dilaksanakan dalam tahap prakontraktual pada perjanjian pendahuluan jual beli rumah karena ketiga tahapan kontrak selalu mengandung itikad baik. Dalam jual beli rumah ada perjanjian pendahuluan yang mendahului perjanjian jual beli yang sesungguhnya. Perjanjian pendahuluan itu tetap mempunyai kekatan mengikat berdasarkan kejujuran. Perlindungan hukum yang dapat digunakan konsumen ketika apa yang diperjanjikan oleh developer tidak tercantum dalam perjanjian pendahuluan adalah ketentuan Keputusan Menteri Negara Perumahan Rakyat No. 09/KPTS/M/1995.